Double Expectations: Law Enforcement Workers and Dilemmas on Handling Drug Use at the Street Level - Quadros Rigoni, Rafaela de (International Journal of Criminology and Sociology, 2017)
This paper analyses law enforcement workers’ experiences when transforming policies for crack cocaine and heroin into practice. It focuses on dilemmas workers have and choices they make when approaching drug users. Grounded theory principles and ethnographic techniques were used to gather and analyse in depth interviews and extensive participant observations of 20 workers across the cities of Amsterdam (Netherlands) and Porto Alegre (Brazil). The comparative analysis enables to explore the impact of different socio-economic and political environments on workers’ practices around drug use. Three areas in which law enforcement workers reported to have dilemmas concern workers’ choices on how to deal with violence; choices between being tough or friendly towards users; and on defining their role on curbing public nuisance. If a first sight shows differences between the cities, in a closer look interesting similarities appear. When deciding upon approaching drug users, law enforcement workers drift between order and care approaches. At the street level, different contexts produce ambiguities and workers’ experiences question the etic reductionism in simple dichotomies of care vs. order approaches. From this closer perspective, similarities appear more clearly, as well as counterpoising perspectives to the stereotypical views of Dutch and Brazilian workers.